Self-study assisted cognitive therapy for PTSD: a case study. - Wild, J; Ehlers, A (2010)
BACKGROUND: Research has demonstrated that Cognitive Therapy for PTSD (CT-PTSD), a version of trauma-focused cognitive-behavioural therapy developed by Ehlers and Clark's group (2000), is effective and feasible when offered in weekly and intensive daily formats. It is unknown whether patients with post-traumatic stress disorder (PTSD) could engage in and benefit from self-study assisted cognitive therapy, which would reduce therapist contact time. OBJECTIVES: This case report aims to illustrate this possibility. DESIGN: A patient with PTSD and comorbid major depression, who developed these problems following a road traffic accident, was treated in six sessions of cognitive therapy with six self-study modules completed in-between sessions. The patient made a complete recovery on measures of PTSD, anxiety, and depression as assessed by self-report and independent assessment. CONCLUSION: Self-study assisted cognitive CT-PTSD reduced the therapist contact time to half of that normally required in standard CT-PTSD. This highlights the potential feasibility and therapeutic benefits of self-study modules in the brief treatment of PTSD. Further research is required to systematically evaluate the acceptability and efficacy of brief self-study assisted CT-PTSD.